Internalisasi Jiwa Kepemimpinan Santri Berdasarkan Nilai-Nilai Moderasi Beragama di Pondok Pesantren Al-Amien Prenduan Sumenep - Fajriyah, Fajriyah; Sutrisno, Andri (Proceedings of Annual Conference for Muslim Scholars, 2023)
Islamic boarding school is an Islamic educational institution in Indonesia with different characteristics and education systems from other formal education. And one of the proofs of the difference is about improving the character of being ready to lead and ready to be led with the nuances of islamic teachings. This research is categorized in the form of descriptive qualitative research with the type of field research. To get the revelant data in this study. Researchers used three data collection techniques, namely observation, interviews and documentation. The analysis uses data reduction, data presentation and data verification. So that in the research, getting conclusion, namely the al-amien Islamic boarding school, it was founded in 1952 AD. By kyai Jauhari Chotib, the sprit student leadership in cultivating a character is ready to lead and ready to be led by externalization, objectivity and internalization. Meanwhile, the activities that help in improving this character are student group leadership training, leadership and management training, basic scouting proficient courses, and student organizations. Also the supporting and inhibiting factors are because there are strengths and opportunities, as well as weaknesses and challenges.